Rainfall Infiltration Process of a Rock Slope with Considering the Heterogeneity of Saturated Hydraulic Conductivity - Zhang, Qingqing; Wang, Laigui; Zhang, Huabin (Frontiers in Earth Science, 2022)
In order to analyze the effects of rainfall events on the stability of an open-pit rock slope, with considering the spatial variability of saturated hydraulic conductivity, based on the unsaturated seepage theory and the random filed theory, modified functions of the unit saturation, the hydraulic conductivity (k) and the shear strength parameters are established for unsaturated slope, by using FISH and the non-intrusive stochastic method. A saturated-unsaturated seepage random field model is proposed. And then the impacts of the rainfall intensity, the rainfall duration and the spatial variability of saturated hydraulic conductivity (ks) on the infiltration process and stability of the unsaturated rock slope are analyzed. The results show that the proposed model can estimate rainfall infiltration of rock slope accurately. Rainfall mainly affects the seepage field in the shallow layer of the slope, where a transient saturated zone can be formed. With the development of the rainfall duration, the weight of the rock mass increased, the matric suction reduced, the negative pore pressure, the degree of saturation and the infiltration depth of the rock slope increased, and the water in the slope root connects with the initial water table gradually, the unsaturated zone shrinks, which causes the safety factor of the model decreases, but the trend of change slows down gradually. As the rainfall intensity strengthened, the infiltration depth increased and the safety factor of the slope reduced, while the changing rate increases first and then decreases. Increasing the correlation length of k can reduces the infiltration depth and safety factor of the slope. Increasing the variation coefficient of k will increase the infiltration depth, while the safety factor of the slope decreases. The infiltration depth and safety factor of the slope are most affected by rainfall duration, but its sensitivity to the variability coefficient of k will be strengthened when the rainfall intensity exceeds the infiltration capacity. This conclusion can provide reference significance for the risk estimation of slope geological hazards, which are induced by the rainfall infiltration.